Bulk Density Response and Experimental Study of Pulsed Neutron-Gamma Density Logging - Wang, Hu; Yue, Aizhong; Zhang, Xiaolei; Tang, Jizhou; He, Xuxin; Luo, Xiang; Han, Bo (Frontiers in Earth Science, 2022)
The pulsed neutron-gamma density logging technique is used to measure the bulk density of formations based on the detection of gamma rays from the inelastic scattering of neutrons in the formations. However, the induced gamma ray source is regarded as a function of neutron transport and cannot be considered a “point” source. Due to the high energy level of gamma rays, the attenuation of inelastic gamma rays is affected by Compton scattering and pair production. Therefore, bulk density can be measured using inelastic gamma rays while considering the effects of neutron transport and pair production. In this paper, a novel density measurement method that uses a completely different response model is proposed to improve the accuracy of density measurement. The process of neutron-gamma density measurement is divided into the neutron transport group and the gamma ray transport group according to the neutron-gamma coupled field theory. A novel density estimation algorithm is derived from the diffusion equation and the gamma ray attenuation law. The accuracy and specification of density measurement are investigated through the Monte Carlo simulation and the calibration of test pits. Theoretical and experimental analyses show that neutron transport and gamma ray transport are not entirely independent of each other in pulsed neutron-gamma density measurement. The newly developed model can effectively enable the inelastic gamma rays to conform to the gamma ray attenuation law and keep the measurement accuracy at ±0.025 g/cm3. Moreover, neutron-gamma density is insensitive to the porosity and lithology of the formation. The proposed novel algorithm successfully establishes the calculation model for the relationship between inelastic gamma rays and bulk density, providing a new perspective for density measurement in pulsed neutron density logging.